2013
DOI: 10.1097/hjh.0b013e3283649b4d
|View full text |Cite
|
Sign up to set email alerts
|

Effects of telmisartan and linagliptin when used in combination on blood pressure and oxidative stress in rats with 2-kidney-1-clip hypertension

Abstract: Inhibition of type 4 dipeptidyl peptidase with linagliptin did not counter BP-lowering effects of ARB in 2k1c rats. Linagliptin reduced lipid and protein oxidation in 2k1c rats, and this effect was BP-independent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 50 publications
4
32
1
Order By: Relevance
“…To address this concern, a recent study tested whether linagliptin affected BP when used in combination with the angiotensin receptor blocker (ARB) telmisartan in a model of renal hypertension. In contrast to the previous studies showing that DPP-4i therapy countered the BP-lowering effects of ACEi (86,87,121), the BP-lowering effects of telmisartan were not countered by linagliptin and tended to further improve BP in a rat model of renovascular hypertension (33). This study suggests the possibility that hypertension, renal function, and glycemic control may be more effectively managed in patients with T2DM treated with a combination of ARB/DPP-4i as opposed to ACEi/DPP-4i.…”
Section: Dpp-4i and Vasculoprotectioncontrasting
confidence: 83%
“…To address this concern, a recent study tested whether linagliptin affected BP when used in combination with the angiotensin receptor blocker (ARB) telmisartan in a model of renal hypertension. In contrast to the previous studies showing that DPP-4i therapy countered the BP-lowering effects of ACEi (86,87,121), the BP-lowering effects of telmisartan were not countered by linagliptin and tended to further improve BP in a rat model of renovascular hypertension (33). This study suggests the possibility that hypertension, renal function, and glycemic control may be more effectively managed in patients with T2DM treated with a combination of ARB/DPP-4i as opposed to ACEi/DPP-4i.…”
Section: Dpp-4i and Vasculoprotectioncontrasting
confidence: 83%
“…DPP-4 inhibitors were found to have renal beneficial effects in animal models of non-diabetic nephropathy such as 5/6 nephrectomy (Tsuprykov et al 2016) Streptozotocin-induced diabetic CD-1 mice Linagliptin -Reduced plasma cystatin C levels and UACR -Ameliorated kidney fibrosis, glomerular size and mesangial area Kanasaki et al (2014), Shi et al (2015) Diabetic db/db mice Gemigliptin -Suppressed albuminuria -Decreased mesangial expansion -Suppressed podocyte apoptosis -Reduced oxidative damage Jung et al (2015), Moon et al (2016) Glp1r 2-kidney-1-clip hypertension (Chaykovska et al 2013), tacrolimus-induced kidney injury (Lim et al 2015), rat Thy-1 glomerulonephritis model (Higashijima et al 2015) and unilateral ureteral obstruction (Min et al 2014).…”
Section: Dpp-4 Inhibition In Animal Models Of Diabetic Nephropathymentioning
confidence: 99%
“…Of note, a small clinical study suggested that DPP-4 inhibitor treatment with sitagliptin attenuated the hypotensive effect of maximal angiotensin-converting enzyme inhibition via the activation of the sympathetic nervous system 56. A preclinical study in male Wistar rats with hypertension induced by stenosis of the renal artery was undertaken to examine the effects of linagliptin, administered alone and with angiotensin receptor blocker therapy, on blood pressure, renal function, and oxidative stress 57. Results demonstrated that linagliptin administered in combination with telmisartan-normalized blood pressure and reduced oxidative stress.…”
Section: Resultsmentioning
confidence: 99%